PERLINDUNGAN HUKUM TERHADAP DESAINER GRAFIS SEBAGAI PESERTA DALAM LOMBA DESAIN GRAFIS BERDASARKAN UNDANG-UNDANG NOMOR 19 TAIIUN 2002 TENTANG HAK CIPTA - Novi Mayasari (DeKaVe, 2013)
Copyright is essentially a part of intangible/incorporeal property which the ownership isseparated from the ownership of the object. Consequently, the enactment of " the participants' worksbelong to the committee" clause cannot be interpreted as the transfer of both of the property rights andcopyright of the works. This study is aimed to know how the graphic designer as a participant in a graphicdesign competition correlated with the existence of "the participants' works belong to the committee"clause is legally protected.The data in this study were obtained by juridical-normative-empirical- research (mixture study).The data obtained from both the library research and the field research were analyzed using descriptivequalitativeapproach. Descriptive approach analyzes only applied at the description level in which factswere analyzes and presents in a systematic way so that it can be more easily understood and inferred.Qualitative approach doesnot emphasize its analysis on numerical data processed by the statisticalmethod. However it doesnot mean that qualitative approach doesn't use quantitative data. Thequantitative data were used but the emphasis wasnot on the hypothesis testing but rather on the attemptto answer the research question through argumentative and formal ways of thinking.The results of this study indicate that most people, especially graphic designers didn't understandthat property rights and copyright of work are two separate things and they assumed that " theparticipants' works belong to the committee" clause as a transfer of both property and copyright of adesign. Thus often caused problems dealed were generated from the illegal use by the committee such asthe use of the works without the cretor's permission, the committee's decision that the competition had nowinner or that the prize is distributed evenly to all the nominees.Keywords: Copyright, Design, Graphic Design